Latest Trends and New Tools Being Used in Strategic Management - Nábrádi, András; Forest, David; Bittner, Beáta; Kovács, Tünde Zita; Madai, Hajnalka; Nagy, Adrián (International Journal of Engineering and Management Sciences, 2021)
In today’s rapidly changing world, there is an increased need for excellent strategic planning. A firm’s survival may indeed hinge on the firm’s planning process being exemplary. Various aspects of the strategic planning process are under review today as organizations wrestle to compete more effectively in an ever-changing world. This paper reveals and describes five new trends or tools being utilized today by firms to more effectively engage in strategic planning. Specifically, the new trends and tools to be discussed in this paper are as follows: increased need to follow a strategic planning model; increased need to develop quality vision and mission statements; a new improved method for incorporating SWOT analysis into practice. Utilizing two matrices one internal and one external to provide a less biased way to access the current strategy fit with conditions facing the firm. Explain the use of a decision matrix commonly called the QSPM (Quantitative Strategic Planning Matrix) for assessing the relative attractiveness of various strategies being considered for implementation. The purpose of this paper is to familiarize readers with basic new tools and techniques being used by organizations to effectively develop an improved strategic plan for the firm.